2022
DOI: 10.1111/ijfs.15806
|View full text |Cite
|
Sign up to set email alerts
|

In‐vitro digestibility, textural and quality characteristics of ditalini pasta fortified with green banana flour and its type ‐IV modified starch

Abstract: Summary Resistant starch in unripe banana offers a possibility to alter the glycemic properties in convenience foods, such as pasta. In this study, pasta formulations were tried by replacing 30% semolina with varying proportions of green banana flour (GBF) and banana‐modified starch (MS). The effect of substitution on physicochemical and functional properties, including in‐vitro starch digestibility, antioxidant property and consumer acceptability, was evaluated. Among the composite flours, MS recorded higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Kaye Foster-Powell et al (2002) have reported mean GI values of 74 AE 5, against bread and glucose standard, for bananas taken with different degrees of ripeness (raw, slightly ripe, fully ripe and over ripe) in Europe, Canada, the USA and South Africa (10 studies). The differences in physical structure could correspond to the degree of particle breakdown during mechanical processing or oral mastication and thus influence glycemic index of food (Reginio et al, 2020;Keran et al, 2022). Therefore, cooking varieties like Monthan and Kaveri Saba could be added as supplement in processing industry to make low glycemic food products, health drinks and as functional food supplements.…”
Section: In-vitro Starch Hydrolysis and Glycemic Index (Gi)mentioning
confidence: 99%
“…Kaye Foster-Powell et al (2002) have reported mean GI values of 74 AE 5, against bread and glucose standard, for bananas taken with different degrees of ripeness (raw, slightly ripe, fully ripe and over ripe) in Europe, Canada, the USA and South Africa (10 studies). The differences in physical structure could correspond to the degree of particle breakdown during mechanical processing or oral mastication and thus influence glycemic index of food (Reginio et al, 2020;Keran et al, 2022). Therefore, cooking varieties like Monthan and Kaveri Saba could be added as supplement in processing industry to make low glycemic food products, health drinks and as functional food supplements.…”
Section: In-vitro Starch Hydrolysis and Glycemic Index (Gi)mentioning
confidence: 99%
“…The type of resistant starch varies based on the food source. For instance, grains and legumes contain type 1 RS, while raw potatoes and unripe bananas contain type 2 RS (Keran et al ., 2022; Walsh et al ., 2022). Type 1 RS is the physically inaccessible starch protected from cell walls, and type 2 RS is a granular native starch with a high crystalline structure (Karunarathna et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…To address these challenges, bananas can be transformed into semi-finished products, such as starch or flour, which provide advantages such as ease of use and longer shelf life compared to fresh bananas. Banana flour has been utilized in a variety of products, including pasta, bread, cakes, crackers, and cookies [2][3][4][5]. Furthermore, unripe banana flour, also known as green banana flour, is a rich source of starch, comprising resistant starch (RS) and dietary fiber, with potential health benefits when consumed.…”
Section: Introductionmentioning
confidence: 99%